Formation and geminate quenching of singlet oxygen in purple bacterial reaction center - Arellano, Juan B.; Yousef, Yaser A.; Melo, Thor Bernt; Mohamad, Samsun Baharin; Cogdell, Richard J.; Naqvi, K. Razi (Elsevier, 2007)
The phosphorescence of singlet oxygen (1X*) photosensitized by the carotenoidless reaction center (RC) of Rhodobacter sphaeroides R26.1 has been investigated, using H2O and D2O as the suspending media. To enhance (under neutral conditions) the triplet quantum yield of the special pair P870 (P) by the radical pair mechanism, the quinone acceptor QA was removed by means of a chemical treatment. The phosphorescence signal fits the functional form P0[exp (t/s) exp(t/f)], regardless of whether 1X* is sensitized by P or M (where the dagger denotes triplet excitation and M is a water-soluble molecule). The time constant f was identified with the decay time of 1X*; when P is the sensitizer, one finds fð1Þ P ¼ 3:3 0:3 ls, and fð2Þ P ¼ 34 3 ls, where the superscripts 1 and 2 refer to H2O and D2O, respectively; the corresponding values for sensitization by M (in the absence of RC) are fð1Þ M ¼ 3:7 0:4 ls, and fð2Þ M ¼ 75 5 ls. The addition of RC’s to the solution of M in D2O reveals that the RC is a quencher of 1X*; however, for equal concentrations of the RC, fð2Þ P < fð2Þ M , showing that 1X* is deactivated, after its entry into the suspending medium, mainly by the solvent or the same RC which acts as the sensitizer. The values of sP are similar in both solvents, ca. 2 ls, but this time constant does not figure in the disappearance of P, which follows a bi-exponential course, a1exp(t/s1) + a2exp(t/s2). The time constants s1 and s2 (72 ± 5 ls and 12 ± 1 ls, respectively) as well as the factor a2 are insensitive to the oxygen content, and quenching of P is manifested only through a threefold reduction in the magnitude of a1; these data imply the absence of dynamic quenching and heterogeneity of the RC. The mean lifetime of 1X* inside the protein matrix is identified with sP, and the absence of a prompt component in the phosphorescence signal rationalized by proposing that the radiative decay of 1X* within the RC is much slower than that in an aqueous environment.